Study of Characteristic of Used Tire, Asphalt, and RHDPE Powder Composites as Car Fender Material - Anwar Nurharyanto; Wachid Yahya (Widyagama University of Malang, 2024)
This research aims to determine the effect of composition on used tire powder composites, asphalt, and recycled plastic (rHDPE), on tensile stress. The composite is expected Can be used for fenders on cars. The composition variations in this study were 500 grams of used tire powder, and 100 grams of asphalt, with variations of rHDPE 20, 30, 40, 50, 60, 70, 80, 90, 100, 120, 200, 250, 300, 350, 400 grams. From the tensile test results, the lowest tensile stress was obtained 0.0233 N/mm2 is owned by a composite with a composition of 40-gram rHDPE. For tensile stress. The highest was a composite with a composition of 400-gram rHDPE with a tensile stress value of 0.855 N/ mm2. The tensile test results of factory-made car fenders have a tensile stress of 0.852 N/mm2. From this research, it can be concluded that composites with composition High rHDPE can be used for fenders.